Management of infected gap non-union of the tibia with bone transport over plate - Pundkare, Gopal; Mankar, Pratik (International Journal of Research in Orthopaedics, 2024)
Compound tibia fracture with bone loss is common presentation in Orthopaedics, treatment for which is well described in the literature. Ilizarov technique is commonly used to fill the bone defect with its different modifications which include additional stabilization with IMIL or Plate. We report a case of infected gap nonunion of proximal tibia shaft which was managed with Ilizarov technique along with a stabilizing plate. The purpose of this report is to provide an alternative mode of management for infected of tibia shaft fracture with bone defect.